Legal framework on poverty alleviation: Comparative studies among Malaysia and United States - Chan, Yi Kei (2023)
This study is to determine the legal framework to alleviate poverty in Malaysia and the United States to make a comparative study and also to provide some suggestions to better alleviate poverty in Malaysia. A qualitative method was used in this research to conduct interviews to get professional knowledge from 3 specialists from the field of laws and regulation related to poverty alleviation. After the conduction of interviews with 3 specialists with the sampling method of purposive sampling, the method to analyze data is thematic analysis. Thematic analysis by generating codes and themes to the interviewees’ answers can better determine the main points mentioned in the interview session and gain useful information for this research. Then, several recommendations are made that may inspire the relevant units in Malaysia to come up with better programs or policies to minimize the poverty rate in Malaysia.